The tourist potential of rural areas in Poland - Sabine Baum (Eastern European Countryside, 2011)
This paper critically examines the role tourism can play in the stabilisation and diversification of rural areas using the example of Poland. Based on the literature and statistical data, the past development and current state of rural tourism in Poland is analysed. Then an analytical framework based on Porter (1990) is developed to assess the future tourist potential of Polish rural areas and identify barriers and chances of tourist development. The analysis revealed that the future tourist potential of rural areas in Poland is limited and often overestimated. Considerable deficits on the supply side and poor financial resources are combined with a limited and recently shrinking demand. The economic significance of tourism in most rural areas outside of the traditional tourist destinations has so far been marginal. Rural tourism in Poland can grow on a small scale and in niche markets requiring: 1) sound market research at national level, 2) regional tourism strategies based on an analysis of the seven depicted success factors, 3) organisations and intersectoral partnerships at regional level, and 4) a high level of interest and initiative of the local population to develop creative ideas for supply `bundles' and to overcome the numerous barriers. Rural tourism is not a panacea for the structural problems of rural areas in Poland. The majority of regions - particularly outside of the traditional tourist destinations and far from big cities - will have to base their diversification on more pillars than tourism.
Keywords: 330; rural tourism; Poland; agritourism; tourist potential; Porter; rural development